The effect of peppermint aromatherapy on nausea and vomiting in pediatric patients with acute lymphoblastic leukemia undergoing chemotherapy - Aslikhatul Umriyah; Nopi Nur Khasanah; Kurnia Wijayanti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The incidence of ALL in children continues to rise. One therapy for ALL patients is chemotherapy. However, chemotherapy has unavoidable side effects, such as nausea and vomiting. Aromatherapy using peppermint oil can help chemotherapy patients feel less nauseous and reduce the likelihood of vomiting. Purpose: To determine the effect of peppermint aromatherapy on nausea and vomiting in pediatric patients with acute lymphoblastic leukemia undergoing chemotherapy. Method: Quantitative techniques were used in this study. This study employed a quasi-experimental design with pre- and post-tests for one group. There were 21 participants in this study. We used the infinite population formula for sample calculation. Peppermint aromatherapy was the independent variable in this study using the Wilcoxon test, while nausea and vomiting ratings were the dependent variables. Results: Data analysis using the Wilcoxon Signed Rank Test yielded an Asymp. Sig. (2-tailed) value of 0.000 (p<0.05). This shows that the assessment of nausea and vomiting differed significantly before and after administration of peppermint. Conclusion: Patients in this study who suffered from nausea or vomiting reported less severe symptoms after consuming peppermint, suggesting the study's hypothesis was correct.